Crackers Made from Nagara Bean (Vigna unguiculata L.) and Three-Spot Gourami (Trichopodus trichopterus) Flours as Complementary Food for Stunting Prevention - Andrestian, Meilla Dwi; Dewi, Zulfiana; Oktiyani, Neni; Noraini, Noraini (Department of Technology of Agricultural product (THP) Jambi University, 2026)
Nagara beans (Vigna unguiculata L.) (NB) and three-spot gourami (Trichopodus trichopterus) (TS) can be used as blended flour, namely “Kanasawa” blended flour (KBF). The KBF is developed into complementary food products, such as crackers, namely “Kanasawa Crackers”, to prevent stunting. This study aimed to investigate the sensory quality, proximate and amino acids profile, Calcium and Phosphorus levels of “Kanasawa Crackers” from KBF. This study is an experimental research that used a Complete Random Design with five formulas of proportion between KBF and mocaf flour, namely: C1 (0:100), C2 (25:75), C3 (50:50), C4 (75:25), C5 (100:0). The best crackers formula was selected using de Garmo analysis. The most preferred cracker product is C2. The best Kanasawa crackers formula consisted of 7.81% water, 3.58% protein, 23.68% fat, 4.90% ash, 2.25% crude fibre, 52.09% carbohydrate, 18 types of amino acid, 0.52% Calcium, and 0.56% Phosphorus. “Kanasawa Crackers” with a KBF-to-mocaf flour ratio of 25:75 are suitable as a complementary food to prevent stunting.